Micro‐activities for C programming learning - Godziashvili, Nino (2017)
Programming introduction disciplines have been subject of concern, discussion and study between teachers in many meetings of the courses of Information Technology in the institutions of higher education. This work was created to contribute to the success of these disciplines, seeking to increase motivation and autonomy of students in solving programming exercises. The proposal consists of making micro‐activities based on Webquests where the student has access to a carefully selected content that will give support for a second phase, the development of a set of increasingly complex tasks. This thesis is focused in C Programming Language classes and discuss how to implement webquest on those classes in order to improve the pedagogical project. This document will also describe the structure of WebQuest and discuss the experiments conducted with students in a classroom.